Detection of hybrids in nature: application to oaks (Quercus suber and Q. ilex). (Heredity, 2009)
Powerful and accurate detection of first-generation (F1) hybrids and backcrosses in nature is needed to achieve a better understanding of the function and dynamics of introgression. To document the frequency of ongoing interspecific gene exchange between two Mediterranean evergreen oaks, the cork oak (Quercus suber) and the holm oak (Q. ilex), we analyzed 1487 individuals originating from across the range of the two species using eight microsatellite loci and two Bayesian clustering approaches (implemented in the programs STRUCTURE and NEWHYBRIDS). Simulated data were used to assess the differences between the two clustering methods and to back up the choice of the threshold value for the posterior probability to discriminate admixed from pure individuals. We found that the use of STRUCTURE resulted in the highest power to detect hybrids, whereas NEWHYBRIDS provided the highest accuracy. Irrespective of the approach, the two species were clearly distinguished as independent genetic entities without any prior information. In contrast with previous reports, we found no evidence for unidirectional introgression. The overall hybridization rate was very low (<2% of introgressed individuals). Only two individuals were identified as F1 hybrids and five as early backcrosses. This work shows that the combined application of the two complementary Bayesian approaches and their systematic validation with simulations, fit for the case at hand, helps gain resolution in the identification of admixed individuals.

Formation of Acutissimin A in red wine through the contact with cork (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2006)
This study shows that when cork material gets in contact with wine, the elagitannins which exist in the cork material (namely one called vescalagin) react with the catechins present in the wine, producing, among others, Acutissimin A, which is an anti-tumoural agent about 250 times more potent than one of the most common anti-cancer drugs clinically used (VP-16). So, the contact of wine samples without the barrel winemaking stage (oak contact) was carried out with cork in order to determine the presence of Acutissimin A. After a contact time of about 30 min, 150 min and 6 days, Acutissimin A was detected in all samples containing cork. In the samples in which the contact was with oak wood, in our conditions, it was not possible to detect Acutissimin A.

La diversidad en las especies forestales: un cambio de escala. El ejemplo del alcornoque (Ecosistemas, 2006)
Diversity in forest tree species: a change in the scale. The case study of cork oak. The strategies for conservation of biodiversity have a major lack in widespread tree species. While the rule in herbaceous/shrublike taxa is ensure the maintenance of interspecific diversity, the changing ability of tree species relies on intraspecific diversity. Cork oak is an example of long-lived, widespread species not considered as threatened. However, cork oak inhabits several sites, with different population histories and ecological constraints frequently unknown. Thus, menaces are more cryptic, allowing cork oak?s regional or local extinction. Conservation strategies should focus in maintaining cork oak?s intraspecific diversity and the processes that generate it, as it is the introgression with other Quercus species

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.

ESTRUCTURA Y EVOLUCIÓN DE DOS MASAS MIXTAS DE FRONDOSAS PROCEDENTES DE UN ANTIGUO MONTE ADEHESADO (III Congreso Forestal Español Congreso, 2001)
The presence of an important number of deciduous Central European species in Hayedo de Montejo makes it to be considered a singular place in Madrid. Past traditional practices conditioned the present characteristics of this forest. Two mixed deciduous stands were chosen for its study, both formed by a stratum of old-growth trees and another made up of poles. A vegetation inventory was made around twenty old-growth trees. The influence in the structure and evolution of the stand composed by poles was studied. The species of old-growth tree and the distance were relevant on the structure of the stand grown around them.

Relaciones hídricas en procedencias de QUERCUS SUBER L. (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.

Genetic variation in central and marginal populations of Quercus suber L. (SILVAE GENETICA, 1999)
Eighteen spontaneous populations of cork oak (Quercus suber) from Spain (14), Portugal (1), Morocco (1) and Italy (2), were surveyed at 14 loci from 12 enzyme systems. Percentage of polymorphic loci (64%), mean number of alleles (2.07), and mean expected heterozygosity (0.158) values were within the ranges described for the genus. Populations from the central range of the species and from peripheral areas were evaluated, and differences between these two kinds were assessed. Significant lower diversity (number of alleles and expected heterozygosity) was found for the most isolated and small size populations in contrast to central forests, showing the existence of mechanisms maintaining the levels of diversity even in some ;isolated stands. Interpopulation diversity (F-st) is 3.3%, indicating extensive gene flows or recent postglacial expansion. A possible recent bottleneck is detected in two populations by comparing actual with expected heterozygosity from the number of detected alleles.

Cork hygroscopic equilibrium moisture content (European Journal of Wood and Wood Products, 1998)
This work is related to the establishment of the curves of cork moisture content in hygroscopic equilibrium (HEM curves), which allow to predict the moisture content of cork planks, one of the most important parameters in cork trading and processing. HEM curves for 20 ~ and 40 ~ based on an empirical model related to experimental data, were mathematically treated in order to set a series of curves in steps of 5 ~ These curves were transformed in a more usual display of the hygroscopic equilibrium mois- ture content, for the most common temperature and hu- midity ranges and tested against experimental data using two cork types.

Effect of hot pressing densification on the cellular structure of black agglomerated cork board (European Journal of Wood and Wood Products, 1994)
Samples of black cork agglomerate boards were observed by scanning electron microscopy, prior and after different densifi- cations. These boards were densified under conditions previous- ly defined, and were observed in two directions, parallel and per- pendicular to the compression axis. The relationship between the average cell wall distance and the compression applied was stud- ied and it was found that the maximum densification is achieved with a pressure of ca. 3 MPa. Some aspects of the influence of densification treatments on the chemical composition of the material were also broached.